2011
DOI: 10.1016/j.rmed.2011.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medical and psychological treatment of depression in patients with COPD – A review

Abstract: Chronic Obstructive Pulmonary Disease (COPD) is a chronic inflammatory lung disease characterized by progressive and only partially reversible symptoms and by considerable negative consequences such as reductions in functional status and quality of life. Comorbid depression is highly prevalent in patients with COPD and related to a worse course of the disease. Despite its negative impact, depression often remains unrecognized and untreated in COPD patients. This review summarizes the current state of findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 63 publications
5
51
0
Order By: Relevance
“…One study [54] reported a large effect size for nortriptyline (Cohen's d -1.07) compared with placebo [10]; however, as only 30 patients completed the study it was strongly underpowered. Due to even more serious methodological limitations of the remaining studies no firm conclusions can be drawn concerning TCAs in patients with comorbid depression and COPD.…”
Section: Effects Of Antidepressants Effects Of Tricyclic Antidepressantsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study [54] reported a large effect size for nortriptyline (Cohen's d -1.07) compared with placebo [10]; however, as only 30 patients completed the study it was strongly underpowered. Due to even more serious methodological limitations of the remaining studies no firm conclusions can be drawn concerning TCAs in patients with comorbid depression and COPD.…”
Section: Effects Of Antidepressants Effects Of Tricyclic Antidepressantsmentioning
confidence: 99%
“…Due to even more serious methodological limitations of the remaining studies no firm conclusions can be drawn concerning TCAs in patients with comorbid depression and COPD. In addition, the acceptability of TCAs in this patient group is clearly limited by their side-effects (especially anticholinergic and antihistaminergic side-effects such as sedation) [10].…”
Section: Effects Of Antidepressants Effects Of Tricyclic Antidepressantsmentioning
confidence: 99%
See 3 more Smart Citations